2017
DOI: 10.3233/isp-170131
|View full text |Cite
|
Sign up to set email alerts
|

On the damping coefficient of laminated glass for yacht industry

Abstract: After a long period in which the most attractive characteristic of a motor yacht was represented by her maximum speed, nowadays the target has moved towards comfort on board which became the fundamental parameter to deal with in the yacht design process.Noise and vibration, together with seakeeping behaviour, became the fundamental subjects on which the research effort of shipyards and technical offices turned on. Since many years the Department of Electrical, Electronic, Telecommunication Engineering and Nava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…During the structural design of yachts, vibration analyses are also performed to check whether vibrations in the structure, originating from excitation sources such as engines, propellers and generators, are below acceptable levels. Yachts designers are motivated to keep vibrations in the structure to a minimum to reduce noise levels inside the yacht and improve the comfort of passengers (Boote et al 2017;Vergassola & Boote 2020).…”
Section: Yacht Structural Designmentioning
confidence: 99%
See 1 more Smart Citation
“…During the structural design of yachts, vibration analyses are also performed to check whether vibrations in the structure, originating from excitation sources such as engines, propellers and generators, are below acceptable levels. Yachts designers are motivated to keep vibrations in the structure to a minimum to reduce noise levels inside the yacht and improve the comfort of passengers (Boote et al 2017;Vergassola & Boote 2020).…”
Section: Yacht Structural Designmentioning
confidence: 99%
“…Vibration and noise inside the yacht should also be considered during the structural design of large glass panels. It has been shown that the vibration of window panes can significantly contribute to noise levels in a cabin when resonating with excitation sources on the ship (Boote et al 2017).…”
Section: Glass Strength and Stiffnessmentioning
confidence: 99%